Small GTPase Rab14 down‐regulates UT‐A1 urea transport activity through enhanced clathrin‐dependent endocytosis. Issue 10 (24th June 2013) - Su, Hua; Liu, Bingchen; Fröhlich, Otto; Ma, Heping; Sands, Jeff M.; Chen, Guangping
Abstract : The UT‐A1 urea transporter plays an important role in the urinary concentration mechanism. However, the molecular mechanisms regarding UT‐A1 trafficking, endocytosis, and degradation are still unclear. In this study, we identified the small GTPase Rab14 as a binding partner to the C terminus of UT‐A1 in a yeast 2‐hybrid assay. Interestingly, UT‐A1 binding is preferential for the GDP‐bound inactive form of Rab14. Coinjection of Rab14 in Xenopus oocytes results in a decrease of UT‐A1 urea transport activity, suggesting that Rab14 acts as a negative regulator of UT‐A1. We subsequently found that Rab14 reduces the cell membrane expression of UT‐A1, as evidenced by cell surface biotinylation. This effect is blocked by chlor‐promazine, an inhibitor of the clathrin‐mediated endocytic pathway, but not by filipin, an inhibitor of the caveolin‐mediated endocytic pathway. In kidney, Rab14 is mainly expressed in IMCD epithelial cells with a pattern identical to UT‐A1 expression. Consistent with its role in participating in clathrin‐mediated endocytosis, Rab14 localizes in nonlipid raft microdomains and codistributes with Rab5, a marker of the clathrin‐mediated endocytic pathway. Taken together, our study suggests that Rab14, as a novel UT‐A1 partner, may have an important regulatory function for UT‐A1 urea transport activity in the kidney inner medulla.—Su, H., Liu, B., Fröhlich, O., Ma, H., Sands, J. M., Chen, G., Small GTPase Rab14 down‐regulates UT‐A1 urea transport activity through enhanced clathrin‐dependent endocytosis. FASEB J. 27, 4100–4107 (2013). www.fasebj.org